2016
DOI: 10.1007/s00706-016-1887-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of naphthalimide-functionalized polynorbornenes

Abstract: Highly fluorescent and photostable (2-alkyl)-1H-benzo[de]isoquinoline-1,3(2H)-diones with a polymerizable norbornene scaffold have been synthesized and polymerized using ring-opening metathesis polymerization. The monomers presented herein could be polymerized in a living fashion, using different comonomers and different monomer ratios. All obtained materials showed good film-forming properties and bright fluorescence caused by the incorporated push–pull chromophores. Additionally, one of the monomers containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…It has been reported that PNB obtained by nickel catalysts could be dissolved in chlorobenzene at room temperature in the 2000s, and the solubility and processability of PNB have been improved. 5,7 Introducing polar groups [8][9][10][11] or exible chains 12,13 into the PNB backbone has become an effective means of solving the problem. The design and synthesis of particularly efficient and stable catalysts is very important for the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PNB obtained by nickel catalysts could be dissolved in chlorobenzene at room temperature in the 2000s, and the solubility and processability of PNB have been improved. 5,7 Introducing polar groups [8][9][10][11] or exible chains 12,13 into the PNB backbone has become an effective means of solving the problem. The design and synthesis of particularly efficient and stable catalysts is very important for the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…A noticeable advantage of the optical platform of 1,8-naphthalimide is the possibility of adjusting the optical properties by varying substituents in the 4th position of the naphthalimide nucleus. For example, a replacement of nitrogen atom by an oxygen allows to shift the fluorescence maximum to the blue range of spectrum [64].…”
Section: Methodsmentioning
confidence: 99%
“…Functional polymers that are able to detect pH attract considerable attention because of their potential application in biology. A series of sensing polymers were prepared, in which naphthalimide derivatives were copolymerized with different monomers such as methyl methacrylate, styrene, 2‐hydroxyethyl methacrylate, [ 56 ] dimethylbicyclo[2.2.1] hept‐5‐ene‐2,3‐dicarboxylate [ 57 ] and acrylamide. Alkylpiperazine derivative of naphthalimides belong to the most popular structures, since they show best sensitivity, even in the complex media.…”
Section: Sensors For Cationsmentioning
confidence: 99%